PENDEKATAN FENOMENOLOGI DALAM STUDI ISLAM DAN RELEVANSINYA TERHADAP DERADIKALISASI AGAMA DI PERGURUAN TINGGI - Muhamad Risqil Azizi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2017)
The idea of religious radicalism has in fact entered in colleges. Without aim-ing at simplistis, the emergence of this radicalism indicates a methodological problem in understanding religion (Islam). A normative-puritanistic ap-proach model can influence the view of the religious phenomena seen in society. The religious phenomenon must ultimately have a negative appraisal and the perpetrators involved in the phenomenon should be branded as ka-fir and heretical. To respond to the negative consequences of this under-standing, it needs to be balanced with a clear-sighted approach in view of the religious phenomenon. In this case, the phenomenology approach through its epochic principle finds its relevance in efforts to deradicalize religious un-derstanding, particularly in college.